CHECK, PLEASE! ON THE MARITAL DEBTS IN SOUTHEAST EUROPEAN LEGAL SYSTEMS - Tešić, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
Apstract: Divorce is often described as one of the most mentally challenging experiences a person can face. In addition to intense emotional distress, divorce has significant legal consequences. One of them, the distribution of marital property, is a frequent subject of discussion in court practice and legal theory. On the other hand, liability for the marital debts is not so often at the focus. On the basis of the above, one could speculate whether only spouses with a positive balance sheet (assets exceeding liabilities) get divorced. In practice, however, it is very common for divorcing spouses to be over - indebted. Moreover, debt is, in some cases, the main trigger or one of several important reasons that have led to divorce. In addition to gambling debts, which have traditionally been a leading cause for divorce, bank debts resulting from excessive credit card use have also become increasingly frequent. Furthermore, debts to mortgage institutions should be emphasised as being especially socially dangerous due to the inherent risk of losing the family home. Some of these obligations may have been created by one of the spouses before the marriage, or they may have been incurred during the marriage by one of the spouses or by both spouses jointly. The role of the court is to divide marital property and debts between the divorcing spouses without affecting the legal position of their creditors in any way. Legal science is there to navigate the court practice in order to achieve equitable distribution between spouses.
Keywords: Personal debts.- Community debts.- Аppropriate family needs.- Joint and several liability.- Right of recourse.